Risk assessment for health of the population in Kyiv from atmospheric air pollution PM2.5 (Environment & Health, 2022)
Objective: Risk assessment for the health of the population in Kyiv from air pollution PM2.5.Materials and methods: There were 24826 measurements of PM2.5 obtained at a stationary observation post in Kyiv. Statistical indicators of noncommunicable morbidity in the adult population of Kyiv were used for the analysis. The attributive part of the risk of death and the quantity of attributable deaths were calculated using the software package AirQ +.Results: As a result of studies in Kyiv, the average value of daily concentrations of PM2.5 for 3 years was calculated 21.7 µg/m3. The attributive part of the risk of death among adults aged ≥30 years from lung cancer was determined to be 9.59% and among adults aged ≥25 years from chronic obstructive pulmonary disease to be 9.07%. Attributable deaths that were associated with long-term PM2.5 exposure were: 63 (95% CI: 29-93) deaths from lung cancer and 7 (95% CI: 4-10) deaths from chronic obstructive pulmonary disease. This represents 9.6% and 6.7% of all deaths, respectively.
Keywords: air; РМ2.5; chronic obstructive pulmonary disease; lung cancer AirQ +